Impact of Cooperative Membership on Adoption of Improved Goat Production Practices in Chitwan District of Nepal - Neupane, H.; Joshi, N.; Kafle, K.; Adhikari, M.; Kharel, S. (Journal of Agriculture and Environment, 2022)
Lack of proper production practice is identified as constraint in production performance of goats. In this context, this study attempts to assess the impact of cooperative membership on adoption of improved production practices among smallholder goat farmers. The analysis is based on data obtained from in-person interview among 327 cooperative members and 334 non-members. The study employs Poisson regression model with endogenous treatment to address the endogeneity. The findings show that cooperatives strongly facilitate adopting improved production practices among goat farmers. Average treatment effect is 2.607, and the average treatment effect on treated is 2.11 and 1.447 in nearest neighbor matching and inverse probability weighted regression adjustment, respectively. The number of improved practices shows non-linear relation with livestock unit. The number of improved production practices increases with training and decreases with distance from tar road. The finding suggest scope to increase the adoption of improved production practices through cooperative membership.